The Extent of Intergenerational Mobility in Northern Region of Malaysia - Zainal, Zalina; Che Mat, Siti Hadijah; Harun, Mukaramah (2016)
This study presents the analysis of intergenerational social mobility in Northern region of Malaysia by focusing on the phenomenon of rural people getting out of the poverty circle. The analysis is based on OLS estimation to demonstrate the possibility of change between income classes. The findings show that social mobility in Malaysia is higher than in other countries where more space and equal opportunities are enjoyed by all walks of life in the nation.